2023
DOI: 10.1002/tcr.202300023
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal‐Free Aromatic C−H, C−N, C−S and C−O Borylation

Abstract: Aromatic organoboron compounds are highly valuable building blocks in organic chemistry. They were mainly synthesized through aromatic C−H and C−Het borylation, in which transition metal‐catalysis dominate. In the past decade, with increasing attention to sustainable chemistry, numerous transition metal‐free C−H and C−Het borylation transformations have been developed and emerged as efficient methods towards the synthesis of aromatic organoboron compounds. This account mainly focuses on recent advances in tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 125 publications
0
10
0
Order By: Relevance
“…The abundant surface chemistry of MOFs endows them with great potential for hybridization with other functional materials toward S-scheme heterojunctions. 35 Various non-MOF semiconductors such as metal oxides, 40,45,80 metal sulfides, [81][82][83][84] metal phosphides, 85,86 and carbon-based composites 45,64,87 have been involved in synthetic routes including solvothermal treatment and the impregnation method. For example, Tang et al reported a novel CoFe 2 O 4 / iron-based MOF (MIL-101, (MIL = Material Institute Lavoisier)) S-scheme heterojunction photocatalyst by a simple solvothermal method with CoFe 2 O 4 nanoparticles distributed on the surface of MIL-101(Fe) octahedra (Fig.…”
Section: Mof/non-mof Heterojunctionsmentioning
confidence: 99%
“…The abundant surface chemistry of MOFs endows them with great potential for hybridization with other functional materials toward S-scheme heterojunctions. 35 Various non-MOF semiconductors such as metal oxides, 40,45,80 metal sulfides, [81][82][83][84] metal phosphides, 85,86 and carbon-based composites 45,64,87 have been involved in synthetic routes including solvothermal treatment and the impregnation method. For example, Tang et al reported a novel CoFe 2 O 4 / iron-based MOF (MIL-101, (MIL = Material Institute Lavoisier)) S-scheme heterojunction photocatalyst by a simple solvothermal method with CoFe 2 O 4 nanoparticles distributed on the surface of MIL-101(Fe) octahedra (Fig.…”
Section: Mof/non-mof Heterojunctionsmentioning
confidence: 99%
“…Traditionally, organoboron compounds are prepared using highly reactive Grignard reagents or organolithium combined with electrophilic boron species, and hydroboration of olefins and alkynes. 14,15 Recently, a variety of borylation strategies, including C-X Miyaura borylation, 16,17 borylative difunctionalization of olefins and alkynes, 18 C-H borylation, 6,[19][20][21][22][23] transition-metal-free borylation, 24,25 and photoinduced borylation, 7 have been developed. The common boron reagents used in the above borylation reactions include diborane and borane reagents [26][27][28] (Scheme 2).…”
Section: Chun-hua Yangmentioning
confidence: 99%
“…12 Stationary wettabilityregulated materials usually require ex situ multistep treatments or devices for achieving highly efficient separation. Stimulusresponsive separation membranes can effectively prevent oil contamination and achieve continuous on-demand oil/water separation by changing the membrane surface wettability under external stimuli (e.g., pH, 13,14 light, 15−17 temperature, 18−20 electricity, 21,22 magnetism, 23−25 and pressure 26,27 ). Stimulus-responsive hydrogels also exhibit superiority toward complex wastewater (such as multiphase heavy oil/water/light oil mixtures).…”
Section: Introductionmentioning
confidence: 99%